Lexicography As an Independent Theoretical Discipline - Yulchiyeva Dilfuza Zafarjon qizi (Genius Publishing Group, 2022)
The article discusses the theory of lexicography. As it is analyzed that the theory of lexicography, rapidly developing the last three decades, along with the practice of creating new types of dictionaries, is formed as an independent theoretical discipline with its own terminological apparatus in several directions as educational, multilingual, scientific and technical.
Keywords: lexicography; theoretical lexicography; types of dictionaries; dictionaries